Relaxation mechanism of nonpolar (1100) and (1120) surfaces of zinc oxide: ab initio calculations - Usseinov, A.B.; Akilbekov, A.T.; Dauletbekova, A.K. (Publishing House of the KarSU named after E.A.Buketov, 2013)
This paper presents ab initio calculations of non polar (1100) and (1120) surfaces of zinc oxide. It is shown that the (1120) surface more stable than the (1100) surface. Electronic relaxation causes redistribution of charge across the surface, where a considerable covalent contribution to chemical bonding is observed. Analysis of vertical ionic displacements showed a typical relaxation picture: after slab relaxation the surface Zn ions are displaced inwards to the slab center, whereas O ions are slightly shifted in the same direction, thus, the anions lies above the cations that usually observed for metal-oxide surfaces.
Keywords: ab initio calculations; ZnO surface; surface energy